The Frequency of the Modifiable Risk Factors in Young Versus Old Patients of Acute ST Elevation Myocardial Infarction - Javaid, Imran; Rashid, Munir Ahmed; Ramzan, Muhammad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To investigate the frequency of modifiable risk factors of ST elevation myocardial infarction (STEMI) in young and old patients. Study design: Cross sectional observational study Place and duration: Study was conducted at cardiology department of DG Khan Medical College & DHQ Teaching Hospital, DG Khan, from 1st July 2020 to 30th June 2021. in one year duration. Methodology: Data was collected from consecutive 120 patients admitted in ward with diagnosis of STEMI. Patient differentiated on the bases of their age ≤ 40 years and above 40 years. Patient’s complete demographic data was recorded and blood samples were taken for serum cholesterol, HDL level, LDL level and triglycerides. SPSS version 23 was used for data analysis and mean (SD) were calculated for numerical data. Frequency (percentages) was calculated for categorical data. Results: Age was stratified with respect to risk factors and it was seen that history of HTN, history of diabetes mellitus, family history of CD, smoking, elevated cholesterol, elevated triglyceride, decreased HDL and elevated LDL were highly associated except gender. These risk factors were more common in >40 years of age. Conclusion: Modifiable risk factors like cholesterol level, smoking, hypertension have high prevalence in ST elevation myocardial patients. Along with all modifiable risk factors old age increase the chances of STEMI.